The transcriptional landscape of seasonal coat colour moult in the snowshoe hare. Issue 16 (7th June 2017) - Ferreira, Mafalda S.; Alves, Paulo C.; Callahan, Colin M.; Marques, João P.; Mills, L. Scott; Good, Jeffrey M.; Melo‐Ferreira, José
Abstract: Seasonal coat colour change is an important adaptation to seasonally changing environments but the evolution of this and other circannual traits remains poorly understood. In this study, we use gene expression to understand seasonal coat colour moulting in wild snowshoe hares ( Lepus americanus ). We used hair colour to follow the progression of the moult, simultaneously sampling skin from three moulting stages in hares collected during the peak of the spring moult from white winter to brown summer pelage. Using RNA sequencing, we tested whether patterns of expression were consistent with predictions based on the established phases of the hair growth cycle. We found functionally consistent clustering across skin types, with 766 genes differentially expressed between moult stages. "White" pelage showed more differentially expressed genes that were upregulated relative to other skin types, involved in the transition between late telogen (quiescent stage) and the onset of anagen (proliferative stage). Skin samples from transitional "intermediate" and "brown" pelage were transcriptionally similar and resembled the regressive transition to catagen (regressive stage). We also detected differential expression of several key circadian clock and pigmentation genes, providing important means to dissect the bases of alternate seasonal colour morphs. Our results reveal that pelage colour is a useful biomarker for seasonal change but that there is a consistent lag between the main gene expression waves and change in visible coat colour. These experiments establish that developmental sampling from natural populations of nonmodel organisms can provide a crucial resource to dissect the genetic basis and evolution of complex seasonally changing traits.